Identifikasi Potensi Ekowisata Tingkat Kecamatan Di Kabupaten Kutai Kartanegara - Heru Suprapto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
This study aims to determine how much potential can be developed for ecotourism activities. The results showed that the development potential of ecotourism in the subdistrict studied was low, the attraction of natural tourism objects lacked selling value and did not have endemic animals or plants. Respondents belong to negative perceptions of ecotourism development because of a lack of public knowledge about the meaning, purpose and benefits of ecotourism. Keyword : Ecotourism, Benefits Of Ecotourism